THE INTEGRATION OF BANJAR PHILOSOPHY AND THE QUR'AN: A SOLUTION FOR THE RESILIENCE OF THE STRAWBERRY GENERATION - ANWAR FAHMI; Rendy Pradana (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
The contemporary digital era has given birth to the phenomenon of the "strawberry generation," a young generation that is intellectually intelligent but mentally and spiritually fragile, characterized by high levels of anxiety and depression. In the midst of this crisis of mental weakness, Banjar's local wisdom offers an antithesis through the philosophy of 'Haram Manyarah, Waja sampai Kaputing' (never give up, as hard as steel to the end). This article aims to reformulate the philosophy into a Qur'an-based model of mental resilience that can be applied to strengthen the character of the 'strawberry generation'. Using the qualitative-hermeneutical approach of Wilhelm Dilthey (Erlebnis, Ausdruck, Verstehen) and tafsīr mawḍū'ī (thematic interpretation), this study bridges the analysis between cultural texts and revelatory texts. The results of the study show a deep semantic and philosophical harmony between the values of Haram Manyarah and the Qur'anic concepts of ṣabr (active patience) and istiqāmah (consistent steadfastness). This philosophy is positioned as an "interpretation of Nusantara," a manifestation of the life behavior of Qur'anic values in the socio-historical context of the Banjar society. As a contribution, this research offers an integrative character education model that synthesizes local wisdom, Qur'anic pedagogy, and modern psychology as culture-based solutions to overcome mental health crises and strengthen the character of the nation's next generation.